Characterizing the Anchoring Effects of Official Forecasts on Private Expectations - BARRERA CHAUPIS, Carlos R. (Theoretical and Practical Research in Economic Fields; Vol 14 No 1 (2023): TPREF, Volume XIV, Issue 1(27), Summer 2023, 2023)
The paper proposes a method for simultaneously estimating the treatment effects of a change in a policy variable on a numerable set of interrelated outcome variables (different moments from the same probability density function). Firstly, it defines a non-Gaussian probability density function as the outcome variable. Secondly, it uses a functional regression to explain the density in terms of a set of scalar variables. From both the observed and the fitted probability density functions, two sets of interrelated moments are then obtained by simulation. Finally, a set of difference-in-difference estimators can be defined from the available pairs of moments in the sample. A stylized application provides a 29-moment characterization of the direct treatment effects of the Peruvian Central Bank’s forecasts on two sequences of Peruvian firms’ probability densities of expectations (for inflation -π- and real growth -g-) during 2004-2015.